Electronic governance in local governments of Peru: A systematic literature review - Rocío, Nevado Chauca, Merly del (Edelweiss Applied Science and Technology, 2025)
This study aimed to analyze scientific papers published between 2020 and 2025 in the Scopus and SciELO platforms focused on electronic governance in local governments of Peru. A total of 10 articles from these databases were selected and reviewed. It was found that the SciELO database presents a limited amount of research on the study variable. On the other hand, Scopus stands out for having a larger number of publications, which can be attributed to the broader international scope in which the variable is studied and other relevant factors that facilitate its development in these repositories. In conclusion, the promotion of electronic governance in local governments of Peru reveals the need for an inclusive and multifaceted approach, requiring policies that recognize and address the barriers municipalities face in adopting and implementing digital tools. This will not only contribute to improving the quality of local public services but also strengthen governance, fostering more equitable and sustainable development.